2021
DOI: 10.1002/app.50969
|View full text |Cite
|
Sign up to set email alerts
|

Silicone‐based biomaterials for biomedical applications: Antimicrobial strategies and 3D printing technologies

Abstract: Silicone is a synthetic polymer widely used in the biomedical industry as implantable devices since 1940, owing to its excellent mechanical properties and biocompatibility. Silicone biomaterials are renowned for their biocompatibility due to their inert nature and hydrophobic surface. A timeline illustration shows critical development periods of using silicone in varied biomedical applications. In this review, silicone properties are discussed along with several biomedical applications, including medical inser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(64 citation statements)
references
References 57 publications
(187 reference statements)
1
56
0
Order By: Relevance
“…Urinary catheters are mainly based on PUR, and their properties vary depending on the nature of the additives and plasticizers used in their manufacture [36]. Moreover, silicone, polysiloxane, or polydimethylsiloxane [(CH3)2-SiO] polymer chains (Figure 1) with different lengths and molecular weights are attractive synthetic polymers, with suitable thermal stability, resistance to physical aging, flexibility, biocompatibility, and hydrophobic properties [37][38][39][40]. Many approaches are available for the modification and functionalization of the surface of organic or inorganic polymers, such as cold plasma surface treatment, which has been tested to prevent the colonization of bacteria [41,42].…”
Section: Antibacterial and Antiadhesive Coatingsmentioning
confidence: 99%
“…Urinary catheters are mainly based on PUR, and their properties vary depending on the nature of the additives and plasticizers used in their manufacture [36]. Moreover, silicone, polysiloxane, or polydimethylsiloxane [(CH3)2-SiO] polymer chains (Figure 1) with different lengths and molecular weights are attractive synthetic polymers, with suitable thermal stability, resistance to physical aging, flexibility, biocompatibility, and hydrophobic properties [37][38][39][40]. Many approaches are available for the modification and functionalization of the surface of organic or inorganic polymers, such as cold plasma surface treatment, which has been tested to prevent the colonization of bacteria [41,42].…”
Section: Antibacterial and Antiadhesive Coatingsmentioning
confidence: 99%
“…In addition to biocompatibility, silica also displays bioconjugation properties, and silica nanoparticles are commonly introduced as coating materials [ 38 ]. Thus, various approaches have been used in biomedical, diagnostic, and therapeutic applications, particularly for the coating of various medical devices [ 18 , 19 , 39 ]. Furthermore, Wang et al [ 19 ] developed a silica-based antibacterial coating for dental implants and showed that silica nanoparticles and gentamycin could be successfully incorporated without any risk of infection, demonstrating that silica-based materials are applicable as a drug delivery system.…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticles are commonly utilized for electrospray-based coatings; for example, titania (TiO 2 ) effectively inhibits Escherichia coli ( E. coli ) and Staphylococcus aureus ( S. aureus ) adhesion on surfaces owing to the hydrophobic properties of the nanoparticles, as reported in previous studies [ 16 , 17 ]. Moreover, silica (SiO 2 ) shows good biocompatibility and has been developed as coating materials, particularly in biomedical applications, such as urinary catheters and dental implants [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some silicone elastomers are used in biomedical applications due to their biocompatibility. In general, silicone has good UV resistance as well as excellent thermal and chemical resistance [21]. The fabrication of elastomers requires that the material cures or crosslinks through the process of molding.…”
Section: Silicone As Materials To Additively Manufacture Implantsmentioning
confidence: 99%